Fiber-reinforced high-sulfur iron tailing mortar material and preparation method thereof

By adding basalt fibers and polyacrylonitrile fibers to the high-sulfur iron tailing mortar, the resistance problem of the mortar under sulfate corrosion and freeze-thaw cycle is solved, and its performance and service life are significantly improved, and the efficient utilization of resources is achieved.

CN119841601APending Publication Date: 2025-04-18SHANDONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510109702.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

When facing sulfate corrosion and freeze-thaw cycle, high-sulfur iron tailings mortar materials have poor resistance, resulting in deterioration of structural performance and making it difficult to effectively utilize this resource.

Method used

Add appropriate amount of basalt fibers and polyacrylonitrile fibers to the high-sulfur iron tailings mortar to improve the compactness and strength of the mortar through the bridging, cracking and filling of the fibers, and enhance its resistance to sulfate corrosion and freeze-thawing.

Benefits of technology

It significantly improves the resistance to internal and external sulfate coupling corrosion, freeze-thaw and toughness of high-sulfur iron tailings mortar, extends its service life, and achieves efficient resource utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841601A_ABST
    Figure CN119841601A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of building mortar materials, and relates to a fiber-reinforced high-sulfur iron tailing mortar material and a preparation method thereof. The mortar material is prepared from the following raw materials in parts by weight: 3050 to 3150 parts of ordinary Portland cement, 4600 to 4700 parts of standard sand, 4600 to 4700 parts of high-sulfur iron tailings, 34 to 35 parts of basalt fiber, 6 to 7 parts of polyacrylonitrile fiber, 15 to 16 parts of polycarboxylate superplasticizer and 1200 to 1400 parts of water. The basalt fiber and the polyacrylonitrile fiber are doped into the high-sulfur iron tailing mortar, so that the long-age performance, the freezing resistance and the internal and external sulfate coupling erosion resistance of the high-sulfur iron tailing mortar are improved, the relatively strong bridging, crack-resisting and filling effects are exerted, the microstructure in the mortar is effectively improved, the porosity is obviously reduced, and the high-sulfur iron tailing mortar has the advantages of favorable water resistance and favorable water resistance. Compared with the prior art, the high-sulfur iron tailing mortar has the advantages that the number of harmful holes is obviously reduced, the compression resistance, tensile resistance and fracture resistance of a sample are improved, the expansion cracking risk caused by long-age sulfur erosion, freeze-thaw cycle and sulfate dry-wet cycle is greatly reduced, the compactness and strength of the high-sulfur iron tailing mortar are improved, and the durability of the high-sulfur iron tailings is optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resource utilization of high-sulfur iron tailings, and specifically relates to a fiber-reinforced high-sulfur iron tailings mortar material and a preparation method thereof. Background Art

[0002] Iron tailings are solid waste generated during the beneficiation and extraction of valuable components from iron ore. At present, China's annual iron tailings discharge exceeds 800 million tons, but its utilization rate is less than 7%. Iron tailings that cannot be effectively utilized are piled up in large quantities in tailings ponds, which not only occupies land resources, but also causes geological disasters such as landslides and dam breaches. When tailings contain sulfur and heavy metals, the surrounding ecological environment also has a high risk of pollution. Therefore, the effective treatment of high-sulfur iron tailings is a major problem at present. In addition, with the continuous and rapid advancement of China's urban infrastructure construction, the demand for mortar raw materials is also increasing. However, due to environmental factors and the introduction of relevant national environmental protection policies, the mining of natural river sand is restricted. In this context, processing high-sulfur iron tailings into fine aggregate for the preparation of mortar improves the utilization rate of solid waste and helps alleviate the shortage of raw materials.

[0003] Sulfate attack is one of the strongest forms of damage to concrete and mortar structures. It is highly destructive and has a complex deterioration mechanism. In my country, sulfates are widely distributed in saline-alkali land, groundwater, lake water, seawater and other environments. Therefore, sulfate attack damage is a key topic that affects the durability of concrete and mortar structures, and has always been the focus of domestic scholars. At present, scholars generally believe that the destruction process of sulfate attack on mortar structure is mainly that sulfate ions enter the mortar and undergo a series of chemical reactions and physical crystallization with cement hydration products (CSH and calcium hydroxide, etc.), generating expansive substances (AFt and gypsum, etc.), changing the microscopic pore structure of the mortar and causing the macroscopic mortar surface to fall off from the surface to the inside. The resulting expansion stress will lead to the initiation and penetration of internal microcracks, which ultimately manifests as the degradation of the macroscopic mechanical properties of the mortar structure. Therefore, for the sake of safety and economy, it is very necessary to develop concrete and mortar structures with good sulfate erosion resistance.

[0004] my country has a vast area of ​​severely cold regions, and the infrastructure in these regions, such as bridges, roads, water conservancy dams, and building foundations, are frequently subjected to freeze-thaw cycles. Concrete components with poor frost resistance are prone to surface peeling and internal structural damage, which affects their safety and service life. Although domestic and foreign scholars have conducted a lot of research on the frost resistance of concrete, for example, adding antifreeze agents to concrete materials. However, under complex environmental conditions, the technology of concrete frost resistance still needs to be further improved.

[0005] At present, there are studies on adding sulfur-resistant cement or sulfur-resistant admixtures to high-sulfur iron tailings mortar materials to improve resistance to internal and external sulfate erosion, but the improvement effect is limited and the cost is high. Compared with river sand mortar, the physical and mechanical properties of high-sulfur iron tailings are poor. For example, as a brittle material, the mortar material will become more brittle after adding a large amount of iron tailings. In addition, freeze-thaw cycle damage will also significantly increase the brittleness of iron tailings mortar. Therefore, how to improve the sulfate erosion resistance and freeze-thaw resistance of high-sulfur iron tailings mortar materials, and further improve the toughness of the material, has become an urgent problem to be solved in this field. Summary of the invention

[0006] In order to improve the sulfate corrosion resistance, freeze-thaw resistance and toughness of high-sulfur iron tailings mortar materials, it is possible to consider adding an appropriate amount of mixed basalt fiber and polyacrylonitrile fiber to the high-sulfur iron tailings mortar. The bridging, crack resistance and filling effects of the fibers significantly improve the density and strength of the high-sulfur iron tailings, and limit the destructive effects of sulfate corrosion and freeze-thaw cycles. The fiber-reinforced high-sulfur iron tailings mortar material and the preparation method thereof provided by the present invention can not only utilize high-sulfur iron tailings on a large scale, but also improve the high-sulfur iron tailings mortar's resistance to internal and external sulfate coupling sulfate corrosion, freeze-thaw resistance, and toughness, providing a practical solution for waste management and environmental remediation. In view of the deficiencies or improvement needs of the prior art, the present invention provides a fiber-reinforced high-sulfur iron tailings mortar material and a preparation method thereof. The mortar material is specifically prepared by using high-sulfur iron tailings, basalt fibers and polyacrylonitrile fibers to prepare the fiber-reinforced high-sulfur iron tailings mortar material. By adding an appropriate amount of basalt fibers and polyacrylonitrile fibers that play a bridging, crack-blocking and filling role to the iron tailings mortar, the high-sulfur iron tailings mortar has improved resistance to internal and external sulfate coupling erosion, freeze-thaw resistance and toughness, and significantly reduced the deterioration of the quality, porosity, longitudinal wave velocity, strength and microscopic pore structure of the high-sulfur iron tailings mortar caused by sulfate dry-wet cycles. The present invention effectively improves the quality of high-sulfur iron tailings mortar-type building facilities and prolongs their service life. It is a new way to efficiently utilize high-sulfur iron tailings as a resource.

[0007] In order to achieve the above object, the present invention provides the following technical solutions: A fiber-reinforced high-sulfur iron tailings mortar material comprises the following components: 3050-3150 parts of ordinary Portland cement, 4600-4700 parts of standard sand, 4600-4700 parts of high-sulfur iron tailings, 34-35 parts of basalt fiber, 6-7 parts of polyacrylonitrile fiber, 15-16 parts of polycarboxylic acid water reducer, and 1200-1400 parts of water.

[0008] Furthermore, a fiber-reinforced high-sulfur iron tailings mortar material includes the following ingredients: 3090 parts of ordinary Portland cement, 4640 parts of standard sand, 4640 parts of high-sulfur iron tailings, 34.2 parts of basalt fiber, 6.8 parts of polyacrylonitrile fiber, 15.5 parts of polycarboxylic acid water reducer, and 1300 parts of water.

[0009] Furthermore, the ordinary Portland cement has a P·O 42.5, a specific surface area of ​​351 m² / kg, a 3-day compressive strength of 5.4 MPa, and a 3-day flexural strength of 28.6 MPa.

[0010] Furthermore, the standard sand has a quartz content greater than 98%, a water content less than 0.18%, a mud content less than 0.18%, a loss on ignition less than 0.47%, and a fineness modulus of 2.38.

[0011] Furthermore, the high-sulfur iron tailings has a quartz content of 24.7%, a sulfur trioxide content of 15.06%, and a fineness modulus of 1.54.

[0012] Furthermore, the polyacrylonitrile fiber has a length of 12 mm, a diameter of 13 μm, and a density of 1.18 g / cm 3 , the tensile strength is 530MPa, the elastic modulus is 7.2GPa, and the ultimate elongation is 22%.

[0013] Furthermore, the basalt fiber has a length of 6 mm, a diameter of 17 μm, and a density of 2.7 g / cm 3 , the tensile strength is 1650MPa, the elastic modulus is 63GPa, and the ultimate elongation is 2.8%.

[0014] Furthermore, the polycarboxylate water-reducing agent has a water reduction rate of 46%, a water bleeding rate of 22%, and a sodium sulfate content of 0.6%.

[0015] The method for preparing the above-mentioned fiber-reinforced high-sulfur iron tailings mortar material resistant to internal and external sulfate coupling corrosion comprises the following steps: S1. Dry the high-sulfur iron tailings and standard sand at 105±2℃ to constant weight, cool them to room temperature, and sieve them using a standard vibrating sieve machine; S2. Primary mixing: First, mix the high-sulfur iron tailings and standard sand for 1 minute until the particles are evenly distributed; Secondary mixing: Secondly, add cement and fiber in turn, mix for 1 minute and 2 minutes respectively, until evenly distributed; Three stirrings: Finally, add water and polycarboxylate water reducer, and stir with a handheld mixer, first at a low speed of 135r / min for 2 minutes, and then at a high speed of 270r / min for 3 minutes; S3. Manual mixing: The mixture after three stirrings is manually stirred for 10 to 25 seconds until it is uniform, which is the fiber-reinforced high-sulfur iron tailings mortar material.

[0016] The application of the fiber-reinforced high-sulfur iron tailings mortar material is used as: Structural materials: used to manufacture precast concrete components, such as beams, slabs, and columns, to enhance the bearing capacity and durability of building structures; Surface material: used for indoor and outdoor floors, sidewalks, airport runways, etc. to improve wear resistance and skid resistance; Composite wall: used to enhance the crack resistance and stability of wall materials and improve thermal insulation performance; Highway engineering: used for roadbed materials or pavement paving materials to improve the durability and fatigue resistance of roads.

[0017] The mortar samples were placed on a vibration table and vibrated for 10 seconds. Then, all samples were left to stand for 24 hours at a temperature of about 20°C and a humidity of more than 90 RH% before demoulding to obtain hardened samples.

[0018] In summary, the fiber-reinforced high-sulfur iron tailings mortar material and the preparation method thereof provided by the present invention have the following beneficial effects compared with the prior art: 1. The present invention adds basalt fiber and polyacrylonitrile fiber to the iron tailings mortar, improves the resistance of the high-sulfur iron tailings mortar to internal and external sulfate coupling erosion, exerts a strong bridging, crack resistance and filling effect, and effectively improves the microstructure inside the mortar. After the sulfate dry-wet cycle test, the porosity inside the fiber-reinforced high-sulfur iron tailings mortar is significantly reduced, and the number of harmful pores is significantly reduced. Moreover, the compression, tensile and flexural properties of the high-sulfur iron tailings mortar are improved, greatly reducing the risk of expansion cracking caused by the sulfate dry-wet cycle, and by utilizing the synergistic effect of basalt fiber and polyacrylonitrile fiber, the intrusion of water is effectively prevented, and the probability of sulfate ions entering the mortar is reduced, which greatly improves the resistance of the high-sulfur tailings mortar to internal and external sulfate coupling erosion, improves the density and strength of the high-sulfur iron tailings mortar, and then extends the service life of the high-sulfur tailings mortar in saline areas and waters, and greatly improves the economic value of high-sulfur tailings.

[0019] 2. In the preparation method of the present invention, basalt fiber and polyacrylonitrile fiber form a complex fiber network inside the mortar. During the freeze-thaw cycle, when the pore water freezes and expands, the ice crystals will exert pressure on the surrounding mortar matrix. The mixed fibers can provide buffer space from multiple directions to resist this expansion pressure. The rigidity of basalt fiber can provide stable support and limit excessive deformation caused by ice crystal expansion, while the elasticity of polyacrylonitrile fiber can deform to a certain extent with the expansion of ice crystals and absorb part of the pressure. In addition, the mixed fibers can significantly improve the impermeability of the mortar and reduce the penetration rate of water. The mixed basalt fiber and polyacrylonitrile fiber significantly improved the frost resistance and toughness of the high-sulfur iron tailings mortar.

[0020] 3. The fiber-reinforced high-sulfur iron tailings mortar material and preparation method provided by the present invention have sufficient raw material supply, simple production process, and make extensive use of industrial solid waste iron tailings. The basalt fiber and polyacrylonitrile fiber selected by the present invention have the advantages of high performance, low cost, and green environmental protection. Therefore, the present invention not only saves production costs, can reduce the amount of river sand and cement in the mortar, but also realizes the secondary utilization of waste, and has significant economic benefits, social benefits and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram comparing the porosity of the mortar samples of Example 1 of the present invention and the comparative example after performing tests one to three; Figure 2 It is a schematic diagram comparing the longitudinal wave velocities of the mortar samples of Example 1 of the present invention and the comparative example after performing tests 1 to 3; Figure 3 It is a schematic diagram comparing the compressive strength of the mortar samples of the embodiment of the present invention and the comparative example after the tests 1 to 3; Figure 4 It is a schematic diagram comparing the splitting tensile strength of the mortar samples of the embodiment of the present invention and the comparative example after the tests one to three; Figure 5 It is a schematic diagram comparing the flexural strength of the mortar samples of the embodiment of the present invention and the comparative example after tests one to three. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0023] The present invention provides a fiber-reinforced high-sulfur iron tailings mortar material and a preparation method thereof, comprising the following steps: S1. Dry the tailings and standard sand in a forced air drying oven at 105±2℃ to constant weight, wait for them to cool to room temperature, and sieve them using a standard vibrating sieve machine.

[0024] S2. Prepare cement, standard sand, high-sulfur iron tailings, basalt fiber, polyacrylonitrile fiber and polycarboxylate water reducer, as well as corresponding equipment according to design requirements; Primary mixing: First, mix the tailings and standard sand for 1 minute until the particles are evenly distributed; Secondary mixing; secondly, add cement and fiber in turn, mix for 1 minute and 2 minutes respectively, until evenly distributed; Three stirrings: Finally, add water and polycarboxylate water reducer, and stir with a handheld mixer for 5 minutes, including 2 minutes of low-speed stirring at 135 r / min and 3 minutes of high-speed stirring at 270 r / min; S3. Manual stirring: The mixture after three stirrings is manually stirred for 10 to 25 seconds until it is uniformly mixed, which is the fiber-reinforced high-sulfur iron tailings mortar material resistant to internal and external sulfate coupling erosion.

[0025] Preferably, the chemical composition of the high-sulfur iron tailings before mixing is shown in the following table:

[0026] Preferably, after the processing in step S1, the particle gradation of the standard sand and the high-sulfur iron tailings before mixing is as shown in the following figure:

[0027] Preferably, after the treatment in step S1, the physical and mechanical properties of the standard sand and iron tailings before and after mixing are shown in the following table:

[0028] Furthermore, the ordinary Portland cement has a P·O 42.5, a specific surface area of ​​351 m² / kg, a 3-day compressive strength of 5.4 MPa, a 3-day flexural strength of 28.6 MPa, an initial setting time of 230 minutes, a final setting time of 300 minutes, and a sulfur trioxide content of 2.38%.

[0029] Furthermore, the standard sand has a quartz content greater than 98%, a water content less than 0.18%, a mud content less than 0.18%, a loss on ignition less than 0.47%, and a fineness modulus of 2.38.

[0030] Furthermore, the high-sulfur iron tailings has a quartz content of 24.7%, a sulfur trioxide content of 15.06%, and a fineness modulus of 1.54.

[0031] Furthermore, the polyacrylonitrile fiber has a length of 12 mm, a diameter of 13 μm, a density of 1.18 g / cm3, a tensile strength of 530 MPa, an elastic modulus of 7.2 GPa, and an ultimate elongation of 22%.

[0032] Furthermore, the basalt fiber has a length of 6 mm, a diameter of 17 μm, a density of 2.7 g / cm3, a tensile strength of 1650 MPa, an elastic modulus of 63 GPa, and an ultimate elongation of 2.8%.

[0033] Furthermore, the polycarboxylate water-reducing agent has a water reduction rate of 46%, a water bleeding rate of 22%, and a sodium sulfate content of 0.6%.

[0034] The embodiment 1 and the comparative example provided by the present invention are as follows: Example 1 The present embodiment provides a basalt fiber-reinforced high-sulfur iron tailings mortar (named: B0.25P0.05), which includes the following raw material components in parts by weight: 3090 parts of cement, 4640 parts of standard sand, 4640 parts of high-sulfur iron tailings, 34.2 parts of basalt fiber, 6.8 parts of polyacrylonitrile fiber, 15.5 parts of polycarboxylate water reducer, and 1300 parts of water.

[0035] The specifications of the components used in this embodiment are as described above.

[0036] This embodiment also provides a method for preparing the above-mentioned fiber-reinforced high-sulfur tailings mortar, and the preparation method comprises the following process steps: S1. Dry the tailings and standard sand in a forced air drying oven at 105±2℃ to constant weight, wait for them to cool to room temperature, and sieve them using a standard vibrating sieve machine.

[0037] S2. Prepare cement, sand, high-sulfur iron tailings, basalt fiber, polycarboxylate water reducer, and corresponding equipment according to design requirements; Primary mixing: First, mix the tailings and standard sand for 1 minute until the particles are evenly distributed; Secondary stirring; secondly, cement and basalt fiber were added in sequence and mixed for 1 minute and 2 minutes respectively until they were evenly distributed; Three stirrings: Finally, add water and water reducing agent, and stir with a handheld mixer for 5 minutes, which includes 2 minutes of low-speed stirring at 135 r / min and 3 minutes of high-speed stirring at 270 r / min.

[0038] S3. Manual mixing: The mixture after three mixings is manually stirred for 10 to 25 seconds to obtain high-sulfur iron tailings mortar.

[0039] The mortar samples were placed on a vibration table and vibrated in a sealed chamber for 10 seconds. Then, all samples were left to stand for 24 hours at a temperature of about 20°C and a humidity of more than 90 RH% before demoulding.

[0040] Comparative Example This comparative example provides a high-sulfur iron tailings mortar (named: B0P0), including the following raw material components in parts by weight: 3090 parts of cement, 4640 parts of standard sand, 4640 parts of high-sulfur iron tailings, 15.5 parts of polycarboxylic acid water reducer, and 1300 parts of water.

[0041] This comparative example also provides a method for preparing the above-mentioned high-sulfur iron tailings mortar, and the preparation method comprises the following process steps: S1. Dry the tailings and standard sand in a forced air drying oven at 105±2℃ to constant weight, wait for them to cool to room temperature, and sieve them using a standard vibrating sieve machine.

[0042] S2. Prepare cement, sand, high-sulfur iron tailings, polycarboxylate water reducer, and corresponding equipment according to design requirements; Primary mixing: First, mix the tailings and standard sand for 1 minute until the particles are evenly distributed; Secondary mixing: Secondly, add cement and mix for 3 minutes until evenly distributed; Three stirrings: Finally, add water and water reducing agent, and stir with a handheld mixer for 5 minutes, including 2 minutes of low-speed stirring at 135 r / min and 3 minutes of high-speed stirring at 270 r / min; S3. Manual mixing: The mixture after three mixings is manually stirred for 10 to 25 seconds to obtain high-sulfur iron tailings mortar.

[0043] The mortar samples were placed on a vibration table and vibrated in a sealed chamber for 10 seconds. Then, all samples were left to stand for 24 hours at a temperature of about 20°C and a humidity of more than 90 RH% before demoulding to obtain hardened samples.

[0044] In order to demonstrate the long-term performance, resistance to freeze-thaw cycle damage, and resistance to internal and external sulfate corrosion of the iron tailings mortar prepared in the embodiment of the present invention (mixed with 0.25% basalt fiber and 0.05% polyacrylonitrile fiber) and the comparative example (without fiber), the mortar samples prepared in the comparative example and the embodiment are analyzed below.

[0045] Test 1: The hardened specimens were cured in a standard curing box (20±2℃, ≥95RH%) for 28 days and 120 days, and then performance tests were conducted to ensure that they met the building requirements.

[0046] Test 2: The hardened specimens were cured in a standard curing box (20±2℃, ≥95RH%) for 26 days, then dried at 65±5℃ for 48h, and finally cooled to room temperature before the sulfate dry-wet cycle corrosion test.

[0047] The sulfate dry-wet cycle erosion test was carried out in accordance with JTG 3420-2020 "Test Procedures for Cement and Cement Concrete for Highway Engineering". The number of dry-wet cycles in the test was set to 15, 30, 45, 60, 75, and 90 times. The specific steps are: immersion in water (5% sodium sulfate solution) for 15 hours → natural air drying (25°C) for 1 hour → oven drying (65°C) for 6 hours → cooling to room temperature for 2 hours. The dry-wet cycle test was carried out in this order, and the total time for one cycle was 24 hours.

[0048] Test 3: The hardened specimens were cured in a standard curing box (20±2℃, ≥95RH%) for 24 days, then immersed in water for 4 days, and then subjected to freeze-thaw tests after being fully saturated.

[0049] The freeze-thaw cycle test was conducted in accordance with GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete". The instrument used in the test was the TMS 9018-R40 freeze-thaw test system, with the freezing temperature set at -20°C, the melting temperature set at 20°C, and the freeze-thaw time of each cycle set at 6h. The number of freeze-thaw cycles was set at 25, 50, 75, and 100 times.

[0050] According to the Chinese standard JTG 3420-2020 "Test Procedure for Cement and Cement Concrete for Highway Engineering" and GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the porosity, longitudinal wave velocity, compressive strength, splitting tensile strength and flexural strength of iron tailings mortar samples were tested. The results are as follows: Figures 1 to 5 shown.

[0051] (1) Adding basalt fiber and polyacrylonitrile fiber to high-sulfur iron tailings significantly reduces the porosity of high-sulfur iron tailings mortar, increases longitudinal wave velocity, compressive strength, splitting tensile strength and flexural strength, and optimizes the microscopic pore structure. For example, the 120-day compressive strength of the comparative example and the embodiment is 21.42MPa and 36.71MPa, respectively. Compared with the comparative example, the 120-day compressive strength of the embodiment is increased by 71.38%. For another example, the 120-day porosity of the comparative example and the embodiment is 24.38% and 16.37%, respectively. By adding basalt fiber and polyacrylonitrile fiber to high-sulfur tailings mortar, the crack expansion is effectively curbed and the pores are filled, thereby significantly improving the microscopic structure quality of the mortar. With the increase of curing time, the porosity of this composite fiber reinforced iron tailings mortar is significantly reduced, and the number of harmful pores is also greatly reduced. In addition, the mortar's compression, tension and flexural properties have been greatly enhanced, significantly reducing the risk of cracks in high-sulfur tailings in the later stage. Thanks to the synergistic effect of basalt fiber and polyacrylonitrile fiber, the oxidation rate of pyrite is effectively slowed down and the concentration of sulfate is reduced. These improvements significantly enhance the mortar's resistance to internal sulfate erosion, improve the mortar's density and strength, and thus significantly increase its service life.

[0052] (2) The high frost resistance basalt fiber-polyacrylonitrile fiber reinforced iron tailings mortar material sample prepared by adding basalt fiber and polyacrylonitrile fiber in the embodiment has good frost resistance. The addition of basalt fiber and polyacrylonitrile fiber to the iron tailings mortar significantly reduces the degradation effect of freeze-thaw cycles on the porosity, longitudinal wave velocity, strength and microscopic pore structure of the iron tailings mortar. For example, the porosity increase rate after 0 freeze-thaw cycles and 100 freeze-thaw cycles of the comparative example and the embodiment is 15.22% and 6.72%, respectively. For example, the compressive strength after 100 freeze-thaw cycles of the comparative example and the embodiment is 18.24MPa and 28.40MPa, respectively. Compared with the comparative example, the compressive strength of the embodiment after 100 freeze-thaw cycles is increased by 55.70%. The addition of basalt fiber and polyacrylonitrile fiber to the iron tailings mortar exerts a strong bridging, crack resistance and filling effect, effectively improving the microstructure inside the mortar. After 100 freeze-thaw cycles, the porosity inside the fiber-reinforced iron tailings mortar decreased significantly, and the number of harmful pores decreased significantly compared with the sample without fiber. When the tailings mortar undergoes freeze-thaw cycles, its compression, tension and flexural properties will continue to deteriorate with the increase in the number of cycles. However, due to the addition of basalt fiber and polyacrylonitrile fiber, this deterioration trend has been effectively delayed. Freeze-thaw cycles will cause stress changes inside the iron tailings mortar, which can easily cause cracking, which is extremely harmful to the integrity of the mortar structure. The synergistic effect of the two fibers is like building a "protective net" inside the mortar, greatly reducing the risk of cracking and ensuring the safety and frost resistance of the iron tailings mortar.

[0053] (3) The polyacrylonitrile fiber reinforced high-sulfur iron tailings mortar material sample prepared by adding polyacrylonitrile fiber in the embodiment has good resistance to internal and external sulfate coupling erosion. The addition of polyacrylonitrile fiber to the high-sulfur iron tailings mortar significantly reduced the degradation effect of sulfate dry-wet cycles on the porosity, longitudinal wave velocity, strength and microscopic pore structure of the iron tailings mortar. For example, the porosity increase rate after 0 dry-wet cycles and 90 dry-wet cycles of the comparative example and the embodiment was 7.25% and 2.27%, respectively. For example, the compressive strength after 90 dry-wet cycles of the comparative example and the embodiment was 19.37MPa and 29.26MPa, respectively. Compared with the comparative example, the compressive strength of the embodiment after 90 dry-wet cycles was increased by 51.06%. Basalt fiber and polyacrylonitrile fiber formed a three-dimensional network structure in the high-sulfur iron tailings mortar, which played a bridging role in the microcracks in the mortar. When microcracks appear in the mortar due to dry-wet cycles or other reasons, the fibers span across the two ends of the cracks to prevent the cracks from further expanding, thereby effectively delaying or even preventing the formation of macro cracks. After 90 dry-wet cycles, the internal pore structure of the sample without fiber was significantly damaged due to repeated water intrusion and evaporation, and the porosity increased significantly. Among them, the number of harmful pores (large pore size, easy for harmful substances to invade and retain) and multiple harmful pores (large pore size, obvious structural damage) increased. In the fiber-reinforced iron tailings mortar, the fibers limit the generation and expansion of cracks, reduce the internal damage caused by dry-wet cycles, and significantly reduce the porosity. The increase in the number of harmful pores and multiple harmful pores is relatively low. When secondary gypsum and calcium aluminate are produced in the fiber-reinforced tailings mortar due to sulfate erosion, which in turn causes expansion stress, the fibers can bear part of the stress and limit the micro-deformation caused by expansion. By limiting the growth of micro-deformation and pore number, the density and strength of high-sulfur iron tailings mortar are improved, its service life is extended, and the resistance of high-sulfur iron tailings mortar to internal and external sulfate coupling erosion is significantly improved, enabling it to better maintain structural stability and functionality in a sulfate erosion environment.

[0054] Based on the above research results, it can be clearly seen that the high-sulfur iron tailings mortar involved in the present invention has significantly improved its density and strength after the introduction of basalt fiber and polyacrylonitrile fiber. This positive change enables the iron tailings mortar to maintain a more stable performance during long-term maintenance; it exhibits good performance in antifreeze properties, effectively resisting the damage to its structure caused by freeze-thaw cycles; it also performs well in resistance to sulfate erosion, reducing the corrosive effect of sulfate on the mortar. Through the comprehensive improvement of these properties, the key goal of enhancing the safety and durability of iron tailings mortar has been achieved. In addition, the invention has obvious advantages in preparation cost. It not only successfully realizes the effective secondary utilization of solid waste, but also greatly reduces pollution to the environment. It has significant economic and environmental benefits, and has laid a solid foundation for the wide application of iron tailings mortar in related fields.

Claims

1. A fiber-reinforced high-sulfur iron tailings mortar material, characterized in that: It includes the following components: 3050~3150 parts of ordinary Portland cement, 4600~4700 parts of standard sand, 4600~4700 parts of high-sulfur iron tailings, 34~35 parts of basalt fiber, 6~7 parts of polyacrylonitrile fiber, 15~16 parts of polycarboxylic acid water reducer, and 1200~1400 parts of water.

2. The fiber-reinforced high-sulfur iron tailings mortar material according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 3090 parts of ordinary Portland cement, 4640 parts of standard sand, 4640 parts of high-sulfur iron tailings, 34.2 parts of basalt fiber, 6.8 parts of polyacrylonitrile fiber, 15.5 parts of polycarboxylic acid water reducer and 1300 parts of water.

3. A fiber-reinforced high-sulfur iron tailings mortar material according to claim 1 or 2, characterized in that: The ordinary Portland cement has a P·O 42.5, a specific surface area of ​​351 m² / kg, a 3-day compressive strength of 5.4 MPa, and a 3-day flexural strength of 28.6 MPa.

4. A fiber-reinforced high-sulfur iron tailings mortar material according to claim 1 or 2, characterized in that: The standard sand has a quartz content greater than 98%, a water content less than 0.18%, a mud content less than 0.18%, a loss on ignition less than 0.47%, and a fineness modulus of 2.

38.

5. A fiber-reinforced high-sulfur iron tailings mortar material according to claim 1 or 2, characterized in that: The high-sulfur iron tailings has a quartz content of 24.7%, a sulfur trioxide content of 15.06%, and a fineness modulus of 1.

54.

6. A fiber-reinforced high-sulfur iron tailings mortar material according to claim 1 or 2, characterized in that: The polyacrylonitrile fiber has a length of 12 mm, a diameter of 13 μm, and a density of 1.18 g / cm 3 , the tensile strength is 530MPa, the elastic modulus is 7.2GPa, and the ultimate elongation is 22%.

7. A fiber-reinforced high-sulfur iron tailings mortar material according to claim 1 or 2, characterized in that: The basalt fiber has a length of 6 mm, a diameter of 17 μm, and a density of 2.7 g / cm 3 , the tensile strength is 1650MPa, the elastic modulus is 63GPa, and the ultimate elongation is 2.8%.

8. A fiber-reinforced high-sulfur iron tailings mortar material according to claim 1 or 2, characterized in that: The polycarboxylate water reducer has a water reduction rate of 46%, a water bleeding rate of 22%, and a sodium sulfate content of 0.6%.

9. The method for preparing a fiber-reinforced high-sulfur iron tailings mortar material according to claim 1 or 2, characterized in that: The following steps are involved: S1. Dry the high-sulfur iron tailings and standard sand at 105±2℃ to constant weight, cool them to room temperature, and sieve them using a standard vibrating sieve machine; S2. Primary mixing: Mix the high-sulfur iron tailings and standard sand for 1 minute until the particles are evenly distributed; Secondary mixing: Add cement and fiber in sequence, mix for 1 minute and 2 minutes respectively, until evenly distributed; Three stirrings: add water and polycarboxylate water reducer, stir with a hand-held mixer, first at a low speed of 135r / min for 2 minutes, then at a high speed of 270r / min for 3 minutes; S3. Manual mixing: After three stirrings, the mixture is manually stirred for 10 to 25 seconds until it is evenly distributed, which is the fiber-reinforced high-sulfur iron tailings mortar material.

10. The use of a fiber-reinforced high-sulfur iron tailings according to claim 1 or 2, characterized in that: It is used as a structural material for manufacturing precast concrete components, or as a surface material for indoor and outdoor floors, sidewalks, and airport runways, or as a composite wall material, or as a roadbed material or pavement paving material in highway projects.

Citation Information

Patent Citations

  • Method for preparing tailing fiber cement mortar from basalt fibers

    CN117756465A